A study on and types and symptoms of allergies in Basrah -southern Iraq - ali , Wasfi Dhahir Abid; Hameed, Semahir S,; Hasan, Mahfoud Falih; shihab, luay abdulwahid (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
We analyzed the data collected from people participated our questionnaire , persons suffer from different types of allergies in Basrah government southern area in Iraq which characterized by heat humid weather at most year seasons, and the present study aimed to investigate the most common type of allergies and it's relation with the symptoms and season. The results revealed that the most dominant type of allergy was seasonal allergy and less medicines allergy with no significant variation between male and female , and there were strong relation between the type of allergy and the symptoms.